2006
DOI: 10.1073/pnas.0601819103
|View full text |Cite
|
Sign up to set email alerts
|

μO-conotoxin MrVIB selectively blocks Na v 1.8 sensory neuron specific sodium channels and chronic pain behavior without motor deficits

Abstract: The tetrodotoxin-resistant voltage-gated sodium channel (VGSC) Na v1.8 is expressed predominantly by damage-sensing primary afferent nerves and is important for the development and maintenance of persistent pain states. Here we demonstrate that O-conotoxin MrVIB from Conus marmoreus displays substantial selectivity for Nav1.8 and inhibits pain behavior in models of persistent pain. In rat sensory neurons, submicromolar concentrations of MrVIB blocked tetrodotoxin-resistant current characteristic of Na v1.8 but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
143
1
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(153 citation statements)
references
References 35 publications
0
143
1
4
Order By: Relevance
“…Ein Zusammenhang mit der Beobachtung einer "Erwärmung des eiskalten Phantombeins" durch die Ambroxolanwendung am Stumpf von Patient 2 bleibt offen. Auch in Tierversuchen ist eine Na v 1.8-Blockade klar analgetisch wirksam [11,20].…”
Section: Pharmakologie Natriumkanäle Und Analgetische Wirkungenunclassified
See 1 more Smart Citation
“…Ein Zusammenhang mit der Beobachtung einer "Erwärmung des eiskalten Phantombeins" durch die Ambroxolanwendung am Stumpf von Patient 2 bleibt offen. Auch in Tierversuchen ist eine Na v 1.8-Blockade klar analgetisch wirksam [11,20].…”
Section: Pharmakologie Natriumkanäle Und Analgetische Wirkungenunclassified
“…Die Na v 1.8-Blockade, z. B. durch Ambroxol, wird letzlich auch deshalb als Option zur Behandlung neuropathischer Schmerzen betrachtet, weil Untersuchungen mit Na v 1.8-freien Mäusen und Na v 1.8-blockierenden Substanzen eine geringere mechanische, thermische und viszerale Übererregbarkeit im Tiermodel belegen [1,4,11,18,20,21,45,46].…”
Section: Na V 18-expressionunclassified
“…Mutations in Na v 1.7 are found in congenital pain syndromes, and knock-down or inhibition of Na v 1.8 has been reported to reduce neuropathic pain behavior in animals. [73][74][75][76] Surprisingly, neuropathic pain is still present in mice lacking Na v 1.7 or Na v 1.8 (established using a Na v 1.8-driven knock-out strategy) and neuropathic pain behavior is even maintained in mice in which nearly all Na v 1.8-positive nociceptors have been ablated. [77][78][79] Because Na v 1.8-expressing nociceptors also express and release BDNF in the spinal cord, perhaps it is the absence of BDNF that changes pain behavior in mice lacking Na v 1.8-positive sensory neurons, given the role of BDNF and TrkB in the establishment of some types of persistent pain behavior (although maybe not all types of neuropathic pain-at least not in mice).…”
Section: Excitotoxicity: Not Just Glutamatementioning
confidence: 99%
“…The toxic effects of δ-conotoxins were subsequently attributed to a delay of VGSC inactivation in molluscan neurons (Fainzilber et al 1991) through what appears to be a new site on the VGSC (Fainzilber et al 1994). Interestingly, this site has been shown to overlap the μO-conotoxin binding site in rat brain (Ekberg et al 2006), which is not surpising given their similar hydrophobicity and related structures. Since these early investigations, a range of new δ-conotoxins have been isolated with varying selectivity for different mammalian VGSCs (Table 4).…”
Section: -Conotoxinsmentioning
confidence: 99%
“…Given the key role TTX-R sodium channels play in pain pathways (Wood and Boorman 2005), MrVIB was assessed for analgesic activity in animal models of pain. In these studies MrVIB delivered intrathecally was analgesic at doses that produced no local anaesthetic-like inhibitory effects on movement or coordination (Ekberg et al 2006). In a separate study, synthetic MrVIB was again found to be analgesic when delivered subcutaneously to rats (Bulaj et al 2006).…”
Section: O-conotoxinsmentioning
confidence: 99%